Rural Vulnerability In Serbia - Ersado, Lire (The World Bank, 2006)
In the presence of risk and uncertainty, measures such as poverty rates are inadequate to analyze the well-being of poor households. The poor are not only concerned about the current low levels of their income or consumption, but also the likelihood of experiencing stressful declines in these levels in the future. Risks to livelihood are particularly important in rural areas where there is generally high dependence on agriculture and the environment. In this study, the author analyzes the nature, extent, and causes of rural vulnerability in Serbia using panel national household data from the 2002 and 2003 Serbia Living Standard Surveys. He measures rural vulnerability as a function of nonstochastic determinants of poverty as well as exposure to risk. While low levels of consumption (poverty) explain about 70 percent of vulnerability, the author identifies risk and uncertainty as crucial dimensions of rural life in accounting for the remaining 30 percent of household vulnerability. Households and regions with a greater share of their livelihood depending on agricultural activities are more at risk of vulnerability than those with a significantly higher share of their income coming from nonagricultural sources. Dependence on agricultural income is directly associated with higher aggregate risk, underscoring the agricultural sector's lopsided exposure to covariate shocks in general, and the negative impact of the 2003 drought in particular. Rural vulnerability to poverty and risk is also strongly associated with asset ownership and access to markets to mobilize them in time of need